Mixed Epigastric Axial Pattern Flap Following Cutaneous Hemangiosarcoma Excision in a Male Dog - Costa Castro, Jorge Luiz; Peres Albernaz, Vinicius Gonzalez; Huppes, Rafael Ricardo; Ramos da Silva, Sergio Santalucia; Engracia Filho, Jair Rodini; Nardi, Andrigo Barboza de [UNESP] (Univ Fed Rio Grande Do Sul, 2016)
Background: Axial pattern flaps use direct cutaneous arteries to enable closure of a skin defect using a large skin segment. Caudal epigastric axial pattern flaps are highly versatile owing to their wide arc of rotation, which includes the preputial area. The presence of abundant loose and elastic skin allows wider flaps. Hemangiosarcoma (HSA) is a malignant neoplasm of endothelial cells with aggressive local behavior and high metastatic rate; the lungs are the most common site of metastasis. This case report aims to describe the use of a caudal epigastric artery-based flap, with preservation of some cranial epigastric artery branches for penis sparing, following resection of a hemangiosarcoma in the right inguinal region of a male dog. Case: An eight-year-old male Pitt Bull dog was referred with a 15 cm, ulcerated hemangiosarcoma in the right inguinal region, near the prepuce. A similar tumor had been removed from the same location two years before. Previous treatment with oral prednisone did not provide satisfactory results. The patient was suffering from intense chronic blood loss and bacterial infection of the tumor tissue. Thoracic radiographs revealed multiple metastatic nodules. Only mild regenerative anemia was found in blood tests. Considerable reductions in tumor size and in the ulcerated surface, decrease in bleeding, and recovery of appetite were observed after 7 days of administration of piroxicam and cephalexin. Surgical resection of the tumor was performed as a palliative treatment with a minimal safety margin of 2 cm, which spared the penis. An epigastric skin flap incorporating the second mammary gland was performed preserving branches of cranial epigastric arteries, and was rotated 160 to cover the defect created in the right inguinal region and on the body of the penis. A small suture dehiscence, necrosis of the distal border of the flap, seroma, and multidrug-resistant Escherichia coli infection were observed in the postoperative period. Administration of penicillin V and topical collagenase, placement of a passive drain, and a second surgical procedure to correct the dehiscence were necessary to solve postoperative complications. Piroxicambased metronomic chemotherapy was maintained continuously, as the patient would exhibit worsening of overall condition upon discontinuation of medication. One hundred days after the initial presentation, the animal was euthanized owing to the presence of an osteolytic lesion on the vertebral bodies of L3-L4 and L5-L6, which were suggestive of discosponlylitis or axial bone metastasis. Discussion: Since lung metastases were present, penectomy and uretrostomy were not considered an option, and a palliative surgical treatment was performed. In this case report, cranial and caudal epigastric flap presented few complications. Caudal epigastric blood vessels are robust and abundant. Distal necrosis was considered a minor complication and was in accordance with others reports. The multidrug resistant infection was considered a nosocomial infection that arised from a long hospital stay. By inhibiting cyclooxygenase, piroxicam decreases angiogenesis, increases apoptosis, and prolongs disease-free intervals with mild toxicity. An excellent response to preoperative administration of piroxicam was crucial when choosing the postoperative protocol. A significant tumor size reduction and a decrease in chronic bleeding associated to improvement in general health were observed with the piroxicam-based treatment. To our knowledge, this is the first report of a mixed (cranial and caudal) epigastric artery skin flap. This type of flap was considered a good option for correction of large defects in the inguinal region and for preservation of the prepuce and penis.
Keywords: hemangiosarcoma; cranial; caudal; penis; sparing